Students' Perceptions on the Role of Google Translate in Learning English - Suardi Suardi; Tenri Ampareng; Alviani Alviani (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to determine the perceptions of electronics engineering students regarding the role of Google Translate in learning English. The method used in this research is a qualitative method using a questionnaire instrument to obtain student perceptions. The research results show that 64.7% of students use Google Translate quite often, 76.5% said Google Translate helps them in learning English. However, 82.4% said they had quite difficulty understanding the results from Google Translate. However, Google Translate role in increasing understanding of new vocabulary is quite helpful because 72.2% said it was quite helpful. However, around 39.9% said Google Translate could negatively influence grammar learning. So, it can be concluded that Google Translate has a role in learning English, but it is necessary to analyze the results of Google Translate because it still has several weaknesses, especially in grammar.